Wykorzystanie popiołów lotnych z węgla brunatnego w budownictwie komunikacyjnym = Application of brown coal fly-ash in communication engineering - Widuch, Aleksamder; Ćwiąkała, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In order to describe chemical and physical properties of brown coal fly-ash from Konin region, analysis of X-ray radiography and scanning microscopy was used. The article aims to present the possibility of application activated brown coal fly-ash for hydraulic binding agents production, especially - to stabilize foundation soil. Findings on bearing capacity (CBR) and dynamics of growing compressive strength (Rc) of soil and binders mixture, prove its suitability for communication engineering.
Keywords: hydrauliczne spoiwo drogowe; aktywator magnetyczny; popiół lotny z węgla brunatnego; hydraulic binding agents; magnetic activator; brown coal fly-ash